An analysis of the relations among leader - member exchange LMX, organizational learning culture and organizational commitment (Case study: Markazy Province Agricultural Experts) - Amir Alambeigi; Ismael Ahangari; Saeide Azizi (مدیریت دولتی, 2014)
Many previous studies used leader - member exchange to explain the quality relationship between employees and supervisors. However, in previous studies, the mechanism of this theory in creativity is not so clear. Thus, this study defines the role of leaders in creating a culture of organizational learning using normative approach to examine the relationship between communication quality leader - member, organizational commitment and organizational learning culture. The statistical population includes 110 Markazy province's agricultural experts who were selected by convenient sampling methodology. The research instrument was a questionnaire designed to measure the model variables. Its validity was confirmed by a panel of experts. Structural equation modeling was used for data processing. Research empirical results are threefold. First, leader - member exchanging quality has a significant effect on learning culture in organization. Second, there is a significant relationship between the learning culture and organizational commitment. Third, LMX quality has an indirect effect on organizational commitment through extension of learning culture. In conclusion, considering research limitations, some practical implications are provided.